2019
DOI: 10.1523/jneurosci.0479-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Cholinergic Interneurons Are a Novel Target of Corticotropin Releasing Factor

Abstract: Cholinergic interneurons (CINs) are critical regulators of striatal network activity and output. Changes in CIN activity are thought to encode salient changes in the environment and stimulus-response-outcome associations. Here we report that the stress-associated neuropeptide corticotropin releasing factor (CRF) produces a profound and reliable increase in the spontaneous firing of CINs in both dorsal striatum and nucleus accumbens (NAc) through activation of CRF type 1 receptors, production of cAMP and reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 65 publications
7
52
0
Order By: Relevance
“…This notion is supported by our original findings that CRF both potentiates dopamine and facilitates appetitive behaviors when acting in the NAc. In this more recent report, we further show that this effect is, in part, due to activation of muscarinic type 5 receptors (M5) on dopamine neuron projections [3]. We propose that CRF’s potentiation of cholinergic and dopaminergic transmission in the NAc is an underlying mechanism for the positive motivational qualities of acute stressors.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This notion is supported by our original findings that CRF both potentiates dopamine and facilitates appetitive behaviors when acting in the NAc. In this more recent report, we further show that this effect is, in part, due to activation of muscarinic type 5 receptors (M5) on dopamine neuron projections [3]. We propose that CRF’s potentiation of cholinergic and dopaminergic transmission in the NAc is an underlying mechanism for the positive motivational qualities of acute stressors.…”
mentioning
confidence: 77%
“…In a study published two months ago, we showed that CRF type 1 receptors (CRF-R1) are ubiquitously expressed on cholinergic interneurons within the NAc of adult male mice [3]. We found that CRF produces a robust increase in action potential firing in cholinergic interneurons via CRF-R1 activation and cAMP dependent mechanisms [3]. Cholinergic interneurons form dense axonal ramifications, and therefore, through acetylcholine modulation, can act as master regulators of accumbal output.…”
mentioning
confidence: 99%
“…A number of other specific signaling molecules also influence CINs. Corticotrophin‐releasing factor in the NAC or dorsal striatum, for example, can enhance CIN activity (Lemos, Shin, & Alvarez, ). That multiple mechanisms modulate CINs suggests striatal circuitry is setup to tightly regulate acetylcholine signaling, allowing for behavioral effects via enhancement or suppression of dopamine release and MSN activity.…”
Section: Modes Of Striatal Dopamine System Action: Activity and Releasementioning
confidence: 99%
“…The neuropeptide corticotropin-releasing factor (CRF) is released in the brain in response to stress (Cook, 2004 ; Merali et al, 2004 ; Wang et al, 2005 ; Ohmura et al, 2009 ; Holly et al, 2016 ), where it can activate the HPA axis (Vale et al, 1981 ; Rivier and Vale, 1983 ) and/or act at its centrally-expressed receptors CRFR1 and CRFR2 (Steckler and Holsboer, 1999 ; Van Pett et al, 2000 ; Sierra et al, 2015 ; Henckens et al, 2016 ) to direct a vast array of adaptive and maladaptive behavioral responses (Hostetler and Ryabinin, 2013 ). Previous studies demonstrate that, through its actions in the nucleus accumbens (NAc) core, CRF can promote appetitive behaviors (Peciña et al, 2006 ; Lim et al, 2007 ; Lemos et al, 2012 ) and increase dopamine release (Lemos et al, 2012 , 2019 ). However, these effects are modulated by a prior stress experience: following exposure to a stressor, CRF loses the ability to increase mesolimbic dopamine release (Lemos et al, 2012 , 2019 ) and produces an aversive behavioral response (Lemos et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate that, through its actions in the nucleus accumbens (NAc) core, CRF can promote appetitive behaviors (Peciña et al, 2006 ; Lim et al, 2007 ; Lemos et al, 2012 ) and increase dopamine release (Lemos et al, 2012 , 2019 ). However, these effects are modulated by a prior stress experience: following exposure to a stressor, CRF loses the ability to increase mesolimbic dopamine release (Lemos et al, 2012 , 2019 ) and produces an aversive behavioral response (Lemos et al, 2012 ). Importantly, experience-dependent dysregulation of the CRF system has been posited as a major contributor to vulnerability for stress hyperresponsivity as well as addiction- and depression-like behavior (Curtis et al, 1999 ; Liu et al, 2005 ; Beckstead et al, 2009 ; Lemos et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%